The effect of Aloe vela on fibroblast cell growth - Sri Herwlyantl, Sri Herwlyantl (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
The study was designed to Investigate the effect of Aloe vera on fibroblast cell growth in vitro. The fibroblast cell culture in a microplate was prepared from twelve day old chicken embryos. Each well was added with 0.3 cc fibroblast suspension. Various concentrations, i.e: 0.010 g/m1; 0.015 g/ml and 0.020 g/ml of Aloe vera were then added into the well, incubated afterwards for 24, 48 and 72 hours at 37ÃÂ° C and were examined under a phase contrast microscope. The results showed that the density and number of fibroblast were Increased, proportionally to the concentration of Aloe vera. The control wells were added with fibroblast only suspension. In the control groups, however, there was only a slight increased and density of cells occured. In conclusion, Aloe vera could stimulate the fibroblast growth.Keywords: Aloe vera - fibroblast - cell culture - chicken embryo - growth factor